Diagnostic laparoscopy in the cat: 1. Rationale and equipment. Issue 1 (January 2014) - Robertson, Elise; Twedt, David; Webb, Craig
Practical relevance: The integration of minimally invasive techniques into feline practice seems to be an intuitive step forward, especially for those cases where the owner may be reluctant to subject their cat to major surgery 'just for a biopsy'. Although ultrasound is frequently employed as a diagnostic tool in similar cases, this modality can only provide information on gross abnormalities in organ size and shape, echogenicity and internal architecture; even with ultrasound-guided fine-needle aspiration a definitive diagnosis is rarely achieved. So the clinician and owner are left with unanswered questions that are central to the diagnosis, the most appropriate treatment to pursue and the prognosis for the cat. Laparoscopy does require anesthesia and is more expensive than ultrasound; however, when performed correctly, it is only marginally more invasive and vastly more informative, with a proven track record of minimal morbidity. Audience: This article is aimed at all feline practitioners, from first opinion through to the referral setting. It is intended to encourage practitioners untrained in minimally invasive procedures to seek formalized training, especially those who want to expand their diagnostic capabilities. For those already performing minimally invasive surgery, it describes how laparoscopic techniques can be applied to many feline gastrointestinal cases. Evidence base: Information provided in this article is based on published literature, comprising original studies, case review series and textbook chapters, and the authors' own clinical experience.